Comparison of NALC-NAOH processing method with C18-carboxy propyl betaine method for the detection of mycobacterium in sputum - Kumar, G. Amar; Chandrasekaran, S. (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is an infectious disease which remains to be a major public health risk worldwide even after the availability of many highly sensitive diagnostic tools. Early case detection plays an important role in control of the disease which relies solely on the detection of acid-fast bacilli in clinical samples which is low sensitive. Prior decontamination of sputum sample may improve the detection of mycobacterium. Methods: A prospective study was conducted with a total of (N=464) clinically suspected TB patient sputum samples which were collected and processed directly for AFB. From which AFB +ve samples were excluded. The direct AFB-ve (N=279) samples were processed using concentration (NALC, CB-18) and culture (LJ medium). After concentration, smears were examined under oil immersion for acid fast bacilli by ZN staining. Results: Out of 464 sputum samples, 185 direct ZN stain +ve were excluded. Among the ZN-ve (N=279) samples, N= 48 (17.2%) were positive using NALC-NaOH method. The positivity has improved to N=69 (25%) using CB-18 and N=79 (28.3%) using culture (LJ medium). Conclusions: CB-18 is sensitive than NALC-NaOH method and its sensitivity is almost comparable to the gold standard culture using LJ medium. Therefore we conclude that the identification of AFB using CB-18 concentration method can be used in resource limited health care setups which might help us to diagnose the TB at the earliest.